DDX3‐mediated miR‐34 expression inhibits autophagy and HBV replication in hepatic cells. Issue 4 (11th January 2023) - Mishra, Amit Kumar; Hossain, Md Musa; Umar, Mohd; Sata, Teja Naveen; Yadav, Ajay K.; Sah, Amrendra Kumar; Ismail, Md; Nayak, Baibaswata; Shalimar,; Venugopal, Senthil Kumar
Abstract: HBV entry to the host cells and its successful infection depends on its ability to modulate the host restriction factors. DEAD box RNA helicase, DDX3, is shown to inhibit HBV replication. However, the exact mechanism of inhibition still remains unclear. DDX3 is involved in multitude or RNA metabolism processes including biogenesis of miRNAs. In this study, we sought to determine the mechanism involved in DDX3‐mediated HBV inhibition. First, we observed that HBx protein of HBV downregulated DDX3 expression in HBV‐infected cells. Overexpression of DDX3 inhibited HBx, HBsAg and total viral load, while its knockdown reversed the result in Hep G2.2.15 cells. Expression of miR‐34 was downregulated in HBV‐infected cells. Overexpression of pHBV1.3 further confirmed that HBV downregulates miR‐34 expression. Consistent with the previous finding that DDX3 is involved in miRNA biogenesis, we observed that expression of miR‐34 positively corelated with DDX3 expression. miRNA target prediction tools showed that miR‐34 can target autophagy pathway which is hijacked by HBV for the benefit of its own replication. Indeed, transfection with miR‐34 oligos downregulated the expression of autophagy marker proteins in HBV‐expressing cells. Overexpression of DDX3 in HBV‐expressing cells, downregulated expression of autophagy proteins while silencing of DDX3 reversed the results. These results led us to conclude that DDX3 upregulates miR‐34 expression and thus inhibits autophagy in HBV‐expressing cells while HBx helps HBV evade DDX3‐mediated inhibition by downregulating DDX3 expression in HBV‐infected cells.